Rencana Teknis dan Biaya Reklamasi Tambang Batubara di PT Bhadra Pinggala Sejahtera Kecamatan Tabang Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Muhammad Mulya Prasetya; Noor Fauzi Isniarno; Solihin (UNISBA Press, 2023)
Abstract. Coal mining in Indonesia is generally carried out with an open pit mining system so that it has an impact on environmental damage. The government requires holders of mining business permits to repair land disturbed by mining activities. The government has issued a clear policy regarding reclamation, namely PP No. 78 of 2010 concerning